Lady of disguise - Dickerson, Melanie (Nashville, Tennessee : Thomas Nelson, 2024)
England, 1388: All her life, Louisa has dreamed of finding the rumored (3z(BGiant$1 (Bs Treasure,(3y (Ba collection of ancient, lost riches said to be hidden on a mountaintop in Scotland, guarded by a fierce monster. It$1 (Bs a story her father used to tell her, and when he dies and she and her younger sister have to go live with their shiftless, greedy uncle, Louisa is determined to find that treasure. It$1 (Bs the hope that has kept her defying her uncle$1 (Bs efforts to marry her off to the highest bidder. After her uncle starts to parade Louisa$1 (Bs twelve-year-old sister Margaret in front of potential husbands, Louisa realizes she has no time to waste. She disguises herself as a boy and takes off for Scotland. But the road is a harsher place than she$1 (Bd imagined, and she is relieved to find a friend in the knight, Sir Charles, who goes along with her on her journey. Charles is intrigued by this young woman who claims her name is (3z(BJack(3y (Band is set on going to Scotland. He goes along, pretending to believe she is a boy, in order to make sure nothing bad happens to her. As they meet new friends along the road, and as Louisa comes clean about her identity, the pair find themselves falling in love. But what will happen when they reach Scotland? Will they find their independence and the freedom to marry in the form of a buried treasure, or will the monster from Louisa$1 (Bs own past keep the young couple apart?s
Includes discussion questions.
Keywords: Sisters -- Fiction; Quests (Expeditions) -- Fiction; Buried treasure -- Fiction; Middle Ages -- Fiction; Christian life -- Fiction; Historical fiction; Christian fiction; Novels; Young adult fiction